Expansion of a urethritis-associated Neisseria meningitidis clade in the United States with concurrent acquisition of N. gonorrhoeae alleles - Retchless, Adam C. (BMC Genomics, 2018)
BACKGROUND: Increased reports of Neisseria meningitidis urethritis in multiple U.S. cities during 2015 have been attributed to the emergence of a novel clade of nongroupable N. meningitidis within the ST-11 clonal complex, the “U.S. NmNG urethritis clade”. Genetic recombination with N. gonorrhoeae has been proposed to enable efficient sexual transmission by this clade. To understand the evolutionary origin and diversification of the U.S. NmNG urethritis clade, whole-genome phylogenetic analysis was performed to identify its members among the N. meningitidis strain collection from the Centers for Disease Control and Prevention, including 209 urogenital and rectal N. meningitidis isolates submitted by U.S. public health departments in eleven states starting in 2015. RESULTS: The earliest representatives of the U.S. NmNG urethritis clade were identified from cases of invasive disease that occurred in 2013. Among 209 urogenital and rectal isolates submitted from January 2015 to September 2016, the clade accounted for 189/198 male urogenital isolates, 3/4 female urogenital isolates, and 1/7 rectal isolates. In total, members of the clade were isolated in thirteen states between 2013 and 2016, which evolved from a common ancestor that likely existed during 2011. The ancestor contained N. gonorrhoeae-like alleles in three regions of its genome, two of which may facilitate nitrite-dependent anaerobic growth during colonization of urogenital sites. Additional gonococcal-like alleles were acquired as the clade diversified. Notably, one isolate contained a sequence associated with azithromycin resistance in N. gonorrhoeae, but no other gonococcal antimicrobial resistance determinants were detected. CONCLUSIONS: Interspecies genetic recombination contributed to the early evolution and subsequent diversification of the U.S. NmNG urethritis clade. Ongoing acquisition of N. gonorrhoeae alleles by the U.S. NmNG urethritis clade may facilitate the expansion of its ecological niche while also increasing the frequency with which it causes urethritis. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12864-018-4560-x) contains supplementary material, which is available to authorized users.